KESALAHAN PENGGUNAAN KALIMAT EFEKTIF PADA TUGAS KARANGAN DESKRIPSI SISWA KELAS VII A SMP N 06 KOTA JAMBI TAHUN PELAJARAN 2020/2021 - Ayu Lestari; Uli Wahyuni (Universitas Batanghari, 2021)
This study aims to describe an error in using effective sentences based on the criteria of effective sentences in the descriptive writing of class VII A students of SMP Negeri 06 Jambi city academic year 2020/2021. This research is qualitative descriptive. The data in this research is in the form of sentences, words that do not fit the criteria of effective sentences. This data is obtained from the descriptive writing of class VII A students of SMP Negeri 06 Jambi city. Based on the results of the research, it can be concluded that there was an error in the use of effective sentences in the descriptive writing of class VII A students of SMP Negeri 06 Jambi city academic year 2020/2021 based on four criteria of effective sentences, namely the criteria of completeness, alignment, frugality and variety. Of the four criteria of effective sentences, the least description of the student error found in using effective completeness while the most dominant error is in the criteria of frugality. From the results of this research, researcher suggests that students need to pay more attention in writing effective sentences. It is recommended that students pay more attention to effective sentences in essays and other writings.